The Chinese Ring puzzle, the Crazy Elephant Dance puzzle, the b-Spinout puzzle, and Gray codes. Issue 558 (November 2019) - Cooper, Curtis
Abstract : The Chinese Ring puzzle consists of a long loop with a handle on one end and nine rings entwined on the loop (see Figure 1).